Investigation of a mortality cluster in wild adult yellow-eyed penguins (Megadyptes antipodes) at Otago Peninsula, New Zealand. Issue 3 (4th May 2017) - Gartrell, Brett; Agnew, David; Alley, Maurice; Carpenter, Tim; Ha, Hye Jeong; Howe, Laryssa; Hunter, Stuart; McInnes, Kate; Munday, Rex; Roe, Wendi; Young, Melanie
ABSTRACT: We investigated an epidemic mortality cluster of yellow-eyed penguins ( Megadyptes antipodes ) that involved 67 moribund or dead birds found on various beaches of the Otago Peninsula, New Zealand, between 21 January and 20 March 2013. Twenty-four carcases were examined post-mortem. Histological lesions of pulmonary, hepatic and splenic erythrophagocytosis and haemosiderosis were found in 23 of 24 birds. Fifteen birds also had haemoglobin-like protein droplets within renal tubular epithelial cells. Despite consistent histological lesions, a cause of death could not be established. Virology, bacteriology and molecular tests for avian influenza, avian paramyxovirus-1, avipoxvirus, Chlamydia psittaci, Plasmodium spp., Babesia spp., Leucocytozoon spp. and Toxoplasma gondii were negative. Tissue concentrations of a range of heavy metals ( n = 4 birds) were consistent with low level exposure, while examination of proventricular contents and mucus failed to detect any marine biotoxins or Clostridium botulinum toxin. Hepatic concentrations of total polycyclic aromatic hydrocarbons (PAHs) ( n = 5 birds) were similar to background concentrations of polycyclic aromatic hydrocarbons previously found in yellow-eyed penguins from the South Island of New Zealand, but there were significantly higher concentrations of 1-methylnapthelene and 2-methylnapthelene in the birds found dead in this mortality cluster. The biological significance of this finding is unclear. A temporal investigation of the epidemic did not indicate either a common source or propagative epidemic pattern. Although our investigation did not definitively implicate a toxic or infectious agent, we could not rule out causes such as toxic marine organisms or mycoplasmosis. Further investigations should therefore by carried out in the event of future mortality clusters.